Successfully Pregnancy Outcome After LLETZ in Women with Cervical Intraepithelial Neoplasia: A Case Series - Indarti, Junita; Surya, Raymond; Aditya, Reyhan; Ikhsan, Muhammad; Alda, Kristian; Antoniman, Mohammad Agassi (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Human papillomavirus (HPV) has an important role in cervical cancer development and the incidence of cervical intraepithelial neoplasia (CIN) was 1.3–2.7/1000 pregnancies. The HPV and its treatments such as loop electrosurgical excisional procedure (LEEP) or large loop electrosurgical excisional procedure (LLETZ) have an association with poor obstetric outcomes. CASE REPORT: Here, we present four case studies of successful live birth after treatment of CIN. We reported that four patients had been performed LLETZ, with abnormal colposcopy results and liquidbased cytology results were one ASCUS, one ASCH, and two HSIL. The histopathology results were one CIN 1, one CIN 2, and two CIN 3. There was a higher rate of pregnancy for treated women than untreated women. The higher the CIN grades, the more prevalence of cesarean section rate. CONCLUSION: The HPV testing or cotesting at 3-year intervals is recommended after treatment due to the sensitivity of HPV testing. Although pregnancy could delay the progression of precancerous lesions, it is recommended to follow the individualized algorithm in the ASCCP guideline to reduce the risk of cervical cancer progression.